Super Champions, Champions, and Almosts: Important Differences and Commonalities on the Rocky Road - Collins, Dave; MacNamara, Áine; McCarthy, Neil (Frontiers in Psychology, 2016)
The real-world experiences of young athletes follow a non-linear and dynamic trajectory and there is growing recognition that facing and overcoming a degree of challenge is desirable for aspiring elites and as such, should be recognized and employed. However, there are some misunderstandings of this “talent needs trauma” perspective with some research focusing excessively or incorrectly on the incidence of life and sport challenge as a feature of effective talent development. The objective of the study was to examine what factors associated with such “trauma” experiences may or may not discriminate between high, medium and low achievers in sport, classified as super-champions, champions or almosts. A series of retrospective interviews were used with matched triads (i.e., super-champions, champions or almosts) of performers (N = 54) from different sports. Data collection was organized in three phases. In the first phase, a graphic time line of each performer’s career was developed. The second phase explored the specific issues highlighted by each participant in a chronological sequence. The third phase was a retrospective reflection on “traumatic” motivators, coach/significant other inputs and psychological challenges experienced and skills employed. Data suggested qualitative differences between categories of performers, relating to several perceptual and experiential features of their development. No evidence was found for the necessity of major trauma as a feature of development. There was a lack of discrimination across categories of performers associated with the incidence of trauma and, more particularly, life or non-sport trauma. These findings suggest that differences between levels of adult achievement relate more to what performers bring to the challenges than what they experience. A periodized and progressive set of challenge, preceded and associated with specific skill development, would seem to offer the best pathway to success for the majority.